Thermal Analyses for Induction Sintering of Powder Metal Compacts up to Sintering Temperature - Çavdar, U.; Atik, E.; Akgül, M.B.; Karaca, H. (Металлофизика и новейшие технологии, 2014)
Induction sintering is developed as an alternative method to conventional sintering in order to sinter iron-based powder metal (PM) compacts. In this study, the 12 kW power and 30 kHz frequency induction-sintering machine is used for 3 wt.% copper-mixed iron. The effects of different shapes and sizes of the induction coil, and temperature differences on the PM compacts up to sintering temperature are investigated; these parameters are determined both theoretically and experimentally during induction sintering. Iron-based PM compacts are sintered at 1120°C. Induction sintering of iron-based PM compacts are simulated using a program to examine the effects of magnetic flux and temperature distribution in the sample over time. The results are compared with the experimental studies.